THE INFLUENCE OF COMPETENCE AND INCENTIVES ON EMPLOYEE PERFORMANCE AT MIKHALYA TUPPERWARE - Pudjiarti, Emiliana Sri; Andriyansah, Andriyansah; Amsar, Amsar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
Mikhalya Tupperware is a company that sells Tupperware. Employee work performance is beginning to deteriorate, as evidenced by low employee morale in completing tasks. Employees typically have a high school diploma and have received no training. Incentives have problems, such as commissions and overtime incentives that do not work as expected. This study employs quantitative descriptive research methods. The study's total population was 39 employees, with saturated samples used as a sampling technique. Simultaneously, there is a significant influence on the work performance of Mikhalya Tupperware employees of the variables of competence and incentives. While only partially found, the competence variable had a significant effect on Mikhalya Tupperware's work performance. In part, it was discovered that the incentive variable had a significant effect on Mikhalya Tupperware's work performance. According to the findings of this study, the competence variable has a greater impact on Mikhalya Tupperware's work performance than the incentive variable.